Comprehensive review of delays in power transmission projects. Issue 14 (1st November 2016) - Pall, Goutom K.; Bridge, Adrian J.; Skitmore, Martin; Gray, Jason
Abstract : The power transmission (PT) system is at the very heart of the power industry and which is vital to the development of a country. Delays in PT projects have a significant adverse effect on the economic development of a country and although billions of dollars are invested globally in PT projects, costly delays are common. Despite the critical nature of PT, the literature relating to the causes of delays is embryonic, with no theoretical or empirical studies yet conducted to establish the factors involved. This study presents a first step in rectifying this situation. A total of 74 published articles are reviewed that are most closely related to PT projects in order to identify their likely causes of delay. As a result, 82 potential causes of delay are identified and classified into nine major groups. The causes are then ranked in terms of their frequency of occurrence in the literature. Finally, conclusions are drawn concerning the extent to which this review and analysis may form a theoretical framework that can be tested empirically, as well as providing crucial information with recommendation to PT project stakeholders to achieve their key targets including the realisation of the benefits involved.